Persistent Hyperinsulinemic Hypoglycemia in Infancy-A Case Report - Rajan, Nishanth; Kalpana, Jamuna; Gopi, Sundaramoorthy; Mohan, Vishwanathan; Radha, Venkatesan; Krishnan, Lalitha (Journal of Nepal Paediatric Society, 2021)
Persistent hyperinsulinemic hypoglycemia of infancy (PHHI) is one of the commonest reasons for severe, intractable hypoglycemia in neonates. Dysregulated insulin secretion is the major underlying pathogenesis which results in hyperinsulinemia, hypoketonemia and hypofatty acidemia. The management is extremely complicated. Early diagnosis and aggressive management of hyperinsulinemic hypoglycemia is essential for prevention of hypoglycemia induced neuronal injury. Here we describe a baby diagnosed as PHHI who was unresponsive to medical management with diazoxide and underwent near total pancreatectomy. Genetic work up revealed a homozygous termination mutation in ABCC8 gene at amino acid position 1452 with heterozygosity in both parents.